PENGARUH APLIKASI TIKTOK TERHADAP AKHLAK REMAJA SMP DALAM KONTEKS SILA KEDUA PANCASILA : ANALISIS DAMPAK NEGATIF TERKAIT PERUNDUNGAN - Melsy Amelia Simanjuntak; Madhani Nur Syafitri; Dina Mutiara Siregar; Halimatussa'diyah; Risma Maulizar Azzanna; Nita Oktaria Tumangger; Jamaludin Jamaludin (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research aims to determine the influence and negative impact of using the Tiktok application on junior high school students, especially related to the increase in cases of bullying among teenagers which is contrary to the second principle of Pancasila, as well as preventive steps that can be taken which are in line with the values of the second principle. Pancasila to overcome this problem. The results of this research show that the Tiktok application can influence the behavior and morals of teenagers, especially junior high school students, because they can be influenced by acts of bullying towards friends around them and practice them. Apart from that, this other negative impact is of course contrary to the second principle of Pancasila and it is feared that it could erode their social and cultural values and have a negative impact on their identity and behavior in the future. To minimize these actions, preventive efforts are of course needed to prevent this from happening sustainably.